Molecular underpinnings of integrin binding to collagen-mimetic peptides containing vascular Ehlers–Danlos syndrome–associated substitutions - Hoop, Cody L. (J Biol Chem, 2019)
Collagens carry out critical extracellular matrix (ECM) functions by interacting with numerous cell receptors and ECM components. Single glycine substitutions in collagen III, which predominates in vascular walls, result in vascular Ehlers–Danlos syndrome (vEDS), leading to arterial, uterine, and intestinal rupture and an average life expectancy of <50 years. Collagen interactions with integrin α(2)β(1) are vital for platelet adhesion and activation; however, how these interactions are impacted by vEDS-associated mutations and by specific amino acid substitutions is unclear. Here, we designed collagen-mimetic peptides (CMPs) with previously reported Gly → Xaa (Xaa = Ala, Arg, or Val) vEDS substitutions within a high-affinity integrin α(2)β(1)-binding motif, GROGER. We used these peptides to investigate, at atomic-level resolution, how these amino acid substitutions affect the collagen III–integrin α(2)β(1) interaction. Using a multitiered approach combining biological adhesion assays, CD, NMR, and molecular dynamics (MD) simulations, we found that these substitutions differentially impede human mesenchymal stem cell spreading and integrin α(2)–inserted (α(2)I) domain binding to the CMPs and were associated with triple-helix destabilization. Although an Ala substitution locally destabilized hydrogen bonding and enhanced mobility, it did not significantly reduce the CMP–integrin interactions. MD simulations suggested that bulkier Gly → Xaa substitutions differentially disrupt the CMP–α(2)I interaction. The Gly → Arg substitution destabilized CMP–α(2)I side-chain interactions, and the Gly → Val change broke the essential Mg(2+) coordination. The relationship between the loss of functional binding and the type of vEDS substitution provides a foundation for developing potential therapies for managing collagen disorders.